Screening of damage induced by lead (Pb) in rye (Secale cereale L.) - a genetic and physiological approach - ÖZYİĞİT, İBRAHİM İLKER (TAYLOR & FRANCIS LTD, 2016)
The fields in which lead (Pb) finds application in the modern world have increased dramatically in recent years. As a consequence of this intensive utilization of Pb, its toxicity tends to pose more and more environmental problems. The aim of this study was to evaluate the genotoxic potential of Pb and to characterize some physiological parameters in Secale cereale under Pb stress. Plants were subjected to different exposure levels of Pb (0, 100, 200 and 400 mu mol/L) for two weeks. At the end of the experimental period, the effects of Pb exposure on the photosynthetic pigments content (chlorophyll a and b, total chlorophyll, chlorophyll a/b and carotenoids) and genetic material of S. cereale were studied. To evaluate the genotoxic effect of Pb, random amplified polymorphic DNA - polymerase chain reaction (RAPD-PCR) was employed. The obtained results showed alteration in the photosynthetic pigments content and RAPD-PCR profiles of S. cereale grown in the presence of Pb. The alterations in the RAPD-PCR profiles following Pb treatments appeared to be losses of normal bands and occurrences of new bands compared to unexposed plantlets. Overall, the content of chlorophyll a, chlorophyll b, total chlorophyll and carotenoids decreased by 6.68%, 6.08%, 2.89% and 8.57%, respectively, under severe Pb stress (400 mu mol/L).
Keywords: RAPD-PCR; genotoxicity; heavy metal; accumulation; photosynthetic pigments; AMPLIFIED POLYMORPHIC DNA; HEAVY-METALS; OXIDATIVE STRESS; RISK-ASSESSMENT; GROWTH; CADMIUM; TOXICITY; SOIL; POLLUTION; SEEDLINGS